Active Learning session based on Didactical Engineering framework for conceptual change in students' equilibrium and stability understanding. (2nd January 2017) - Canu, Michael; Duque, Mauricio; de Hosson, Cécile
ABSTRACT: Engineering students on control courses lack a deep understanding of equilibrium and stability that are crucial concepts in this discipline. Several studies have shown that students find it difficult to understand simple familiar or academic static equilibrium cases as well as dynamic ones from mechanics even if they know the discipline's criteria and formulae. Our aim is to study the impact of a specific and innovative classroom session, containing well-chosen situations that address students' misconceptions. We propose an example of Active Learning experiment based both on the Didactical Engineering methodology and the Conceptual Fields Theory that aims at promoting a conceptual change in students. The chosen methodology allows, at the same time, a proper design of the student learning activities, an accurate monitoring of the students' rational use during the tasks and provides an internal tool for the evaluation of the session's efficiency. Although the expected starting conceptual change was detected, it would require another activity in order to be reinforced.